MODERN METHODS AND APPROACHES OF TEACHING ENGLISH - Mirzayeva , Nasiba Bakhtiyar kizi (Innovative Development in Educational Activities, 2023)
This article tells us about need of learning English language. For This aim is necessary to use different methods and approaches to teaching of English language. Main methods of teaching English are considered.